Distributed Control of Partial Differential Equations Using Convolutional Reinforcement Learning - Peitz, Sebastian; Stenner, Jan; Chidananda, Vikas; Wallscheid, Oliver; Brunton, Steven L.; Taira, Kunihiko (Physica D: Nonlinear Phenomena)
We present a convolutional framework which significantly reduces the complexity and thus, the computational effort for distributed reinforcement learning control of dynamical systems governed by partial differential equations (PDEs). Exploiting translational equivariances, the high-dimensional distributed control problem can be transformed into a multi-agent control problem with many identical, uncoupled agents. Furthermore, using the fact that information is transported with finite velocity in many cases, the dimension of the agents’ environment can be drastically reduced using a convolution operation over the state space of the PDE, by which we effectively tackle the curse of dimensionality otherwise present in deep reinforcement learning. In this setting, the complexity can be flexibly adjusted via the kernel width or by using a stride greater than one (meaning that we do not place an actuator at each sensor location). Moreover, scaling from smaller to larger domains – or the transfer between different domains – becomes a straightforward task requiring little effort. We demonstrate the performance of the proposed framework using several PDE examples with increasing complexity, where stabilization is achieved by training a low-dimensional deep deterministic policy gradient agent using minimal computing resources.

Insights and Challenges of Co-Simulation-based Optimal Pulse Pattern Evaluation for Electric Drives - Hölsch, Lukas; Brosch, Anian; Steckel, Richard; Braun, Tristan; Wendel, Sebastian; Böcker, Joachim; Wallscheid, Oliver (IEEE Transactions on Energy Conversion)
Keywords: Electrical and Electronic Engineering; Energy Engineering and Power Technology

Time-Optimal Model Predictive Control of Permanent Magnet Synchronous Motors Considering Current and Torque Constraints - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Finite Set Sensorless Control With Minimum a Priori Knowledge and Tuning Effort for Interior Permanent Magnet Synchronous Motors - Brosch, Anian; Tinazzi, Fabio; Wallscheid, Oliver; Zigliotto, Mauro; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

ElectricGrid.jl - A Julia-based modeling and simulationtool for power electronics-driven electric energy grids - Wallscheid, Oliver; Peitz, Sebastian; Stenner, Jan; Weber, Daniel; Boshoff, Septimus; Meyer, Marvin; Chidananda, Vikas; Schweins, Oliver (Journal of Open Source Software)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Pseudo-Labeling Machine Learning Algorithm for Predictive Maintenance of Relays - Winkel, Fabian; Wallscheid, Oliver; Scholz, Peter; Böcker, Joachim (IEEE Open Journal of the Industrial Electronics Society)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Control and Systems Engineering

Fade-Over Strategy for use of Model Predictive Direct Self-Control with Field-Oriented Control - Pena, Mario; Meyer, Michael; Wallscheid, Oliver; Böcker, Joachim (2023 IEEE International Electric Machines and Drives Conference (IEMDC))

Finite-Set Direct Torque Control via Edge Computing-Assisted Safe Reinforcement Learning for a Permanent Magnet Synchronous Motor - Schenke, Maximilian; Haucke-Korber, Barnabas; Wallscheid, Oliver (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Deep Q Direct Torque Control with a Reduced Control Set Towards Six-Step Operation of Permanent Magnet Synchronous Motors - Haucke-Korber, Barnabas; Schenke, Maximilian; Wallscheid, Oliver (2023 IEEE International Electric Machines & Drives Conference (IEMDC))

Gym-Electric-Motor (GEM) Control: An Automated Open-Source Controller Design Suite for Drives - Book, Felix; Traue, Arne; Schenke, Maximilian; Haucke-Korber, Barnabas; Wallscheid, Oliver (2023 IEEE International Electric Machines & Drives Conference (IEMDC))